Analysis of Willingness to Pay For Environmental Services in the Management Planning of the Jero Kerti Waterfall Tourism Object with the Ecotourism Concept - Indrawan, I Nyoman Gde Ary; Basuki, Prayitno (PT FORMOSA CENDEKIA GLOBAL, 2024)
Indonesia has significant natural wealth, with abundant natural resources in it. Tourism is one of the strategic sectors in the development of the regional economy, especially in the waterfall tourism area. Jero Kerti Waterfall, located in Dasan Geria Village, Lingsar District, West Lombok Regency, West Nusa Tenggara, is one of the tourist attractions that is quite popular with the community. Although still in the early stages of ecotourism concept management, Dasan Geria Village has become a Tourism Village area in West Lombok Regency. Suboptimal tourism management can threaten the sustainability of natural resources and the surrounding ecosystem. Therefore, this study aims to calculate the willingness to pay (WTP) value for environmental services to support Jero Kerti Waterfall ecotourism and to determine the factors that influence the WTP value. This study uses a descriptive approach to create systematic, factual, and accurate descriptions and descriptions of the facts, nature, and relationships between the phenomena studied. The sampling technique uses simple random sampling to ensure that every visitor has an equal opportunity to be interviewed. Data were analyzed using the Contingent Valuation Method (CVM) to determine WTP. Analysis of factors affecting WTP values ​​was carried out using a simple regression equation. Data processing used the SPSS application to test validity and classical assumptions, and to determine the effect of independent variables on dependent variables together.